KAFALAH AND RAHN: CONCEPTUAL ANALYSIS AND IMPLEMENTATION IN CONTEMPORARY SHARIA FINANCING - kaharuddin kahar; Fitri Shaganta; Nufzatutsaniah Nufzatutsaniah (Program Studi Ekonomi Syariah IAI Muhammadiyah Bima, 2024)
This study aims to analyze the concept, implementation, and effectiveness of sharia guarantee instruments, namely kafalah and rahn, in the context of contemporary sharia financing. The method used is a literature study with an interpretive-critical approach to examine classical and contemporary sources. The results show that although kafalah and rahn have a strong theoretical foundation, their implementation in Islamic financial institutions faces significant challenges, such as the gap between theory and practice, the need for innovation in the context of globalization and financial technology, and alignment with sharia maqashid. This research highlights the importance of regulatory harmonization, the development of inclusive operational mechanisms, and adaptation to modern technology to increase the effectiveness and compliance of sharia in the sharia financing system. The results are expected to be a significant contribution to the development of a more just, inclusive, and sustainable Islamic economy.